Metal Distribution and Sediment Quality Variation across Sediment Depths of a Subtropical Ramsar Declared Wetland - Tatenda Dalu (Water, 2020)
The study of wetlands is particularly important as these systems act as natural water purifiers and thus can act as sinks for contaminated particles. Wetland sediments are important as they provide an indication of potential contamination across temporal and spatial scales. The current study aimed to investigate the distributions of selected metals and nutrients in different sites in relation to sediment depth, and identify relationships among sediment metals. Significant differences in nutrient (i.e., N, P) and metal (i.e., K, Mg, Na, Fe, Cu, B) concentrations were found across study sites, whereas nutrients (i.e., N, P) and metals (i.e., Ca, Mg, Fe, Cu, Zn) were significantly different with sediment depths. When compared against Canadian sediment standards, most of the assessed metals were within the “no effect” level across the different sites and depths. The K, Ca, and Mg concentration showed extreme contamination across all sites and depths. The enrichment factor values for K, Ca, and Mg showed extremely high enrichment levels for all sites and sediment depths. The Na, Mn, Fe, Cu, Zn, and B concentration showed mostly background enrichment levels. All sediments across the different sites and sediment depths indicated deterioration of sediment quality. Pearson correlations suggest that most metals might have originated in a similar source as that of Mn and B, owing to a lack of significant differences. These results provide baseline information for the general management of the Nylsvley Wetland in relation to sediment metal pollution. The specific sources of metal contaminants also require further elucidation to further inform management efforts.